Výroba modelu jízdního kola s využitím aditivní metody Fused Deposition Modeling - Krobot, Daniel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalářská práce je zaměřena na popis současného stavu problematiky navrhování výrobků, především dostupným technologiím Rapid Prototyping. Práce se zaměřuje na výrobu 3D modelu jízdního kola s využitím grafického programu Autodesk Inventor. Výroba modelu jízdního kola byla realizována na 3D tiskárně uPrint s využitím metody Fused Deposition Modeling. Součástí práce je také technicko-ekonomické zhodnocení.

The thesis is focused on describing the current state of product design issues, in particular available rapid prototyping technologies . The work focuses on 3D model of bicycle using the graphic´s program Autodesk Inventor. Production of the bicycle was made on the 3D printer uPrint byusing methods of Fused Deposition Modeling. The work also contents techno-economic evaluation.
Production of a Bicycle Model Using Additive Method Fused Deposition Modeling
Keywords: Rapid Prototyping; Stereolitografie; Solid Ground Curing; Polyjet; Laminated Object Manufacturing; Fused Deposition Modeling; jízdní kolo; 3D modely.; Rapid Prototyping; Stereolithography; Solid Ground Curing; Polyjet; Laminated Object Manufacturing; Fused Deposition Modeling; Bicycle; 3D Models.